Immunization with OPN5 increased seasonal degradation of reproductive activity in Magang ganders - Jianqiu Pan; Xu Shen; Hongjia Ouyang; Junfeng Sun; Sui Liufu; Danli Jiang; Wenjun Chen; Siyue Peng; Danning Xu; Yunbo Tian; Yunmao Huang; Jianhua He (Poultry Science)
To investigate the regulatory mechanism mediated by hypothalamic OPN5 on seasonal changes in the reproductive activities of domestic geese, 60 Magang ganders in their breeding period were selected for the experiment and evenly divided into an immunization group(OPN5-IM) and a control group. On days 0, 15 and 30, ganders in the immunized group were immunized with OPN5-KLH protein vaccine, and ganders in the control were immunized with the same amount of blank emulsified vaccine. Additionally, 120 female geese were provided to stimulate the reproductive activities of male geese. The results showed that the arrangement of spermatogenic cells was disturbed, the number of sperm decreased, and the testicular weight, seminiferous tubule area, length diameter, spermatogenic epithelium thickness decreased significantly with the natural day length prolonged. Moreover, the concentration of testosterone and LH decreased significantly while PRL increased. The prolonged photoperiod significantly affected the gene expression of GnRH-I, VIP, FSHβ, FSHR, LHβ, PRL, and PRLR in ganders. Specifically, the gene expression of GnRH-I, FSHβ, and LHβ in the hypothalamus and pituitary decreased, while the gene expression of VIP, PRL, and PRLR increased. Following OPN5 immunization, the anti-OPN5 antibody titer of ganders in the OPN5-IM group was notably higher than in the control group. The testicular degeneration was severe in OPN5-IM group compared with the control, as evidenced by a significant reduction in seminiferous tubule area, length diameter, and thickness of spermatogenic epithelium in the immunized group on day 60. Additionally, the concentrations of testosterone and LH were lower in the OPN5-IM group than in the control group, whereas PRL was higher. Moreover, OPN5 immunization significantly affected the expression of GnRH-I, PRL, and PRLR. OPN5 mRNA and protein expression were higher in the immunized group, whereas TRH, DIO2, and TSHR mRNA expressions were lower. However, DIO3 mRNA and protein were up-regulated in the immunized group. In conclusion, our results indicated that the reproductive performance of Magang geese degraded from the breeding to the non-breeding period as daylight was extended. Immunization against OPN5 increased OPN5 expression and down-regulated the TSH-DIO2/DIO3 pathway, further to affect the HPG axis and accelerate the degradation of reproductive activity. Therefore, OPN5 may play an important mediating role in light-regulating seasonal reproductive degradation in Magang geese.